1986
DOI: 10.3109/00498258609043567
|View full text |Cite
|
Sign up to set email alerts
|

The metabolism of14C-oxcarbazepine in man

Abstract: The disposition of the new anti-epileptic agent oxcarbazepine (10,11-dihydro-10-oxo-5H-dibenz[b,f]azepine-5-carboxamide) has been studied in two healthy volunteers following an oral 400 mg dose of 14C-labelled drug. The dose was excreted almost completely in the urine (94.6 and 97.1%) within six days. Faecal excretion amounted to 4.3 and 1.9% of the dose in the two subjects. In the 0-6 days urine samples the biotransformation products have been isolated and identified. 10,11-Dihydro-10-hydroxycarbamazepine (GP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
79
0
8

Year Published

1990
1990
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(87 citation statements)
references
References 13 publications
0
79
0
8
Order By: Relevance
“…Because the metabolism of OXC or MHD barely uses catalytic oxidation by CYP450 (only approximately 4% of MHD is oxidized to the inactive dihydroxy derivative), there is only a small potential for the metabolism of OXC or MHD to be affected by the inducers of CYP [2,5,16] . However, some studies suggest that the classical enzyme-inducing AEDs such as CBZ, PB and PHT may increase the metabolism of MHD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the metabolism of OXC or MHD barely uses catalytic oxidation by CYP450 (only approximately 4% of MHD is oxidized to the inactive dihydroxy derivative), there is only a small potential for the metabolism of OXC or MHD to be affected by the inducers of CYP [2,5,16] . However, some studies suggest that the classical enzyme-inducing AEDs such as CBZ, PB and PHT may increase the metabolism of MHD.…”
Section: Discussionmentioning
confidence: 99%
“…Based on previous research [2,5,15,16] , we first proposed the following assumptions: OXC was completely absorbed (the bioavailability was fixed at 1.0) and metabolized to the same amount of MHD in the mass unit. The first-order conditional estimation method with the η-ε interaction option (FOCE L-B) was used throughout the model building process.…”
Section: Structural Modelmentioning
confidence: 99%
“…In humans, formation of MHD is stereoselective, with the two enantiomers formed in a ratio of 80% (S enantiomer of MHD [(S)-MHD]) to 20% (R enantiomer of MHD [(R)-MHD]) (Flesch et al, 1992). After oral administration of radiolabeled OXC, only 2% of total radioactivity in plasma is due to unchanged OXC, and approximately 70% is due to MHD (Schütz et al, 1986). Minor amounts of oxcarbazepine are transformed in a sulfate conjugate and directly conjugated (Schütz et al, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…Oxcarbazepine is rapidly reduced by cytosolic arylketone reductases to the monohydroxy derivative (MHD) (Fig. 1) (Schütz et al, 1986;Menge and Dubois, 1983). In humans, formation of MHD is stereoselective, with the two enantiomers formed in a ratio of 80% (S enantiomer of MHD [(S)-MHD]) to 20% (R enantiomer of MHD [(R)-MHD]) (Flesch et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Although the precise mechanism by which OXC exerts its antiseizure effect is unknown, it is well documented that OXC is completely adsorbed and extensively metabolized (approximately 70%) by reductase enzymes to its pharmacologically active 10-monohydroxy derivative form eslicarbazepine ((S)-licarbazepine, MHD, Figure 1) [5]. The structure-activity relationships to date have shown that the potency and selectivity of 1 are linked to the N-carboxamido group embodied in the twisted boat conformation of the dibenzoazepine core [6].…”
Section: Open Accessmentioning
confidence: 99%